Progresso genético com a seleção recorrente visando resistência ao mofo branco no feijoeiro - Lima , Gleice Aparecida da Silva (2022)
White mold, caused by the fungus Sclerotinia sclerotiorum (Lib.) De Bary, is one of the main diseases that affect the common bean crop. Obtaining resistant cultivars has been a challenge for breeding programs, due to the low heritability and polygenic nature of the trait. However, recurrent selection has been efficient to accumulate favorable alleles for white mold resistance. Thus, the present work aimed to obtain the cycle XIII and to estimate the genetic progress of the last four cycles of the recurrent selection program for resistance to white mold at UFLA. The 12 most resistant progenies of cycle XII (CXII) were intercrossed to obtain CXIII. After intercrossing, 486 S0 seeds were selected from CXIII, with carioca-type grains, and these were sown and inoculated by the straw test method and evaluated for reaction to the isolate S. sclerotiorum UFLA 27, in greenhouse. The 42 most resistant S0 plants were selected and sown in the field to advance the generations until S0:2. The 42 S0:2 progenies from CXIII were evaluated for their reaction to UFLA 27 isolate in the greenhouse. The five best progenies of cycles X, XI, XII and XIII were selected to compose the trial to estimate the genetic progress (PG), along with four more common checks, two resistant (A195 and Cornell605) and two susceptible (Beryl and IPRCorujinha). The trial consisted of two experiments in DBC, with three replications, and the plot consisting of a 5L pot with three plants, conducted in greenhouse. Each experiment was inoculated with one isolate of S. sclerotiorum, UFLA 27 and UFLA 145. The white mold severity plants were evaluated from the fourth to the ninth day after plant inoculation the area under the disease progress curve (AACPD) was estimated. Comparison of means was performed using Dunnett and Scott-Knott tests. To obtain the Genetic Progress (PG), a linear regression analysis was performed. The S0:2 progenies of CXIII presented the lowest mean scores regarding the reaction to the isolates. A PG in the reduction of disease severity and AACPD, of 4,27 and 3,7% was estimated considering the average of isolates, of 4,62 and 3,56% for UFLA 27 and of 3,96 and 3,82% for UFLA 145, respectively. These results confirm the efficiency of recurrent selection in accumulating favorable alleles even after 13 cycles. The PG of CXIII relative to CXII estimated for reduction in the means of white mold severity score and AACPD was 22,43 and 23,98% considering isolate means 30,13 and 29,32% for UFLA 27 and 14,67 and 18,63% for UFLA 145 respectively. The results point the efficiency of artificial inoculation in the greenhouse to obtain resistant genotypes. Although selection was performed for the UFLA 27 isolate, PG was also observed by inoculating the UFLA 145 isolate, suggesting the accumulated resistance alleles are broad-spectrum, contributing to durable resistance. Therefore, we suggest the selection of progenies 13/40 of CXIII and 53/3 of CXII to advance the generation and possibly obtain common bean lines with high level of resistance adapted to the region, with carioca-type grains.